George Bolster - when will we recognize us - Markonish, Denise; Sacramone, Leanne; Kelleher, Sarah; Walsh, Claire; Kissane, Seán ca. 20. Jh; Russell, Ian 1979- (Hirmer, 2023)
This monograph examines the multidisciplinary practice of conceptual Irish artist George Bolster, who addresses the crises facing our species, and our willingness to live in the past through belief systems. Bolster’s ambitious immersive text and image works encompass film, installation, tapestry and photography
Contributions by Denise Markonish, Leanne Sacramone, Sarah Kelleher, Claire Walsh, Seán Kissane, Ian Alden Russell
Keywords: Bolster, George -- 1972-; Fotografie; Zeitgenössische Kunst; Kunst 21. Jahrhundert; Künstlermonographien; Performance Kunst; Photography; Contemporary Art; Art 21st Century; Artist monography; Performance Art